Anthropometric study of medical students - Balasuriya, P. (Sri Lanka Medical Association. Colombo, 1988)
Stature, sitting height, biacromial diameter, total arm length and foot length were measured in 133 mdical students. Analysis of data showed no ethnic differences in the mean values for measurements in males and females, in contrast to some past studies. Sex differences in the mean values were significant. Stature, sitting height, total arm length showed positive correlation with each pther in both sexes. While the correlation of biocromial diameter with other measurements was low in males, there was no correlation in females. The results indicate that a significant increase in stature since 1937 and 1948 has taken place due to a disproportionate increase in length of the lower limbs compared to the trunk. The upper limbs too appear to show an increase in length proportionate to stature. There is a significant increase in the transverse diameter of the upper end of the trunk. Certain segments of the body bear a constant relation ship to stature in both sexes.
Keywords: Medical Sciences; Body measurements; Physical development; Physiology; Malnutrition